TRIDIMENSIONAL WAVES AT THE INTERFACE OF TWO ELASTIC MEDIA ON CONTACT WITHOUT FRICTION - Sarkisyan, S.V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
The question of presence of Stoneley’s surface waves in three-dimensional statement is considered. Conditions are given at the interface of two half-space corresponding to the contact of two half-space without friction. The investigated problems are simplified by the introduction of potential function with analogue of the plane deformation problems. The characteristic equation is obtained concerning the phase speed of the surface wave, for which the special cases are considered.